Behavior of eccentrically loaded circular concrete-filled steel tube stub columns with localized corrosion - Lin, Siqi; Li, Zhenlin; Zhao, Yan-Gang (Engineering structures, 2023)
•The behavior of eccentrically loaded circular CFST stub columns with localized corrosion was investigated.•The localized corrosion at the mid-height caused more significant capacity deterioration than that at the column ends.•Localized corrosion with γ = 0° and 180° has more adverse effects on the capacity than that with γ = 90°.•A design model was proposed for eccentrically loaded CFST column with localized corrosion. In this paper, 12 concrete-filled steel tube (CFST) stub columns with localized corrosion were tested under eccentric load. The effects of the depth ratio, size and location of localized corrosion, and loading eccentricity on the eccentric compression behavior of circular concrete-filled steel tube stub columns were investigated. A finite element model of circular CFST stub columns with localized corrosion under eccentric load was developed and then parameter analysis was carried out. Based on the experimental and numerical results, it was found that the load bearing capacity decreases with increasing the depth ratio and size of localized corrosion. The localized corrosion at the mid-height caused more significant capacity deterioration than that at the column ends. In addition, the localized corrosion with γ = 0° and 180° has more adverse effects on the capacity of eccentrically loaded CFST columns than that with γ = 90°. Moreover, the localized corrosion with γ = 0° (at compression side) is more harmful than that γ = 180° (at tension side) for the specimens with compression-controlled failure, and vice versa for the specimens with tension-controlled failure. Finally, a design model of eccentrically loaded CFST column with localized corrosion was proposed based on an established equivalent specimen. The results suggested that the proposed model predicted the load bearing capacities with reasonable accuracy.